2009
DOI: 10.1007/s10529-009-0170-7
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of bifidobacteria to lysozyme as a possible selection criterion for probiotic bifidobacterial strains

Abstract: Resistance or susceptibility of bifidobacteria to lysozyme and growth of bifidobacteria in human milk were tested. Susceptible bifidobacterial strains stopped their growth almost immediately after the addition of lysozyme (400 microg/ml), moderately susceptible strains exhibited reduced growth rate, and growth curves of resistant strains were not affected. Strains of human origin were more resistant to lysozyme than animal strains. While strains of B. bifidum grew well in human milk samples, the growth B. anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The susceptibility to lysozyme was tested according to Rada et al (2010). Bacterial growth was determined using Densitometer DEN-1 (Dynex, Prague, Czech Republic) based on the OD 540 values.…”
Section: Tested Strains the List Of Isolates Is Shown Inmentioning
confidence: 99%
“…The susceptibility to lysozyme was tested according to Rada et al (2010). Bacterial growth was determined using Densitometer DEN-1 (Dynex, Prague, Czech Republic) based on the OD 540 values.…”
Section: Tested Strains the List Of Isolates Is Shown Inmentioning
confidence: 99%
“…The results has shown that lactoferrin in iron-limited forms and probiotics incorporated to biotherapeutic products can inhibit the overgrowth of enteric bacteria and so could help to balance of human gut microflora. In another study, Rada et al [19] the growth of bifidobacteria in human milk was investigated. The results showed that both tested strains of B. bifidum grew in all human milk samples in contrast to strains of B. animalis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Direct enzymatic action on the host is unlikely, but allergenicity and impact on the gut microbial ecosystem will require investigation. For example, bifidobacteria were shown to display a variable resistance to lysozyme, and this characteristic was proposed to be a useful criterion for the selection of new probiotic strains [63]. Another indirect effect that should be considered is immune modulation due to the generation of peptidoglycan fragments that may trigger host immune receptors.…”
Section: Future Trends and Research Needsmentioning
confidence: 99%